Pemahaman Masyarakat Muslim Tentang Kedudukan Wali Dalam Pernikahan - Yarmunida, Miti (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to describe the understanding of the muslim community about the position of guardians in Islam. The research method used is descriptive qualitative research. The data is extracted from primary data sources, namely the results of interviews with predetermined informants, secondary data sources are taken from references relevant to this research. The results showed that the majority of people did not understand the position of the guardian in marriage. Thus, the government in the field of Islamic religious education must make the content of the guardian position in Islam. This is very important for the validity of the marriage that will be carried out by both husband and wife and their offspring